PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS XI TSM 4 SMK KESATRIAN PURWOKERTO - salam, yuhda (PREDIKSI (PROFESI PENDIDIKAN INDONESIA), 2023)
This classroom action research aims to improve student learning outcomes by using the Problem Based Learning model in class XI TSM 4 SMK Kesatrian Purwokerto. This research uses the Kemmis and Mc model approach. Taggart consists of two cycles with each cycle consisting of four stages, namely plan, action, observation, reflection. The research subject is class XI TSM 4, totaling 24 students and the object of this research is learning outcomes. Before learning was implemented using the Problem Based Learning model, 15 students (62.5%) did not reach the Minimum Completeness Criteria (KKM). This means that only 9 (37.5%) students reached or exceeded the KKM. At the end of Cycle I, learning outcomes increased, 11 (45.8%) students did not reach the KKM, while 13 (54.2%) other students reached the KKM. At the end of cycle II there was an increase in learning outcomes where of the 24 students in class Therefore, it can be said that the use of the Problem Based Learning learning model can improve students' mathematics learning outcomes in statistics material in class XII TSM 4 SMK Kesastrian Purwokerto.